Critical discourse analysis on women’s position in prohaba daily news texts - Eva Evianda; Ramli Ramli; Mohd Harun (Studies in English Language and Education, 2019)
This research aimed to describe women’s position in Prohaba Daily News texts based on Sara Mills and Theo van Leeuwen perspective of critical discourse analysis, especially the analysis of actor position, exclusion and inclusion. This is a descriptive qualitative research in which data were collected by documentation technique. The data were Prohaba Daily News texts during 2018. The data were analyzed using Sara Mills’ actor position analysis model and Theo van Leeuwen’s exclusion and inclusion analysis. Actor position analysis included subject position and object position. Exclusion analysis included the passivation, nominalization, and substitution of clauses. While the inclusion analysis included differentiation-indifferentiation, objectivity-abstraction, nomination-identification, nomination-categorization, determination-indetermination, assimilation-individualization, and association-disassociation. The results showed that Prohaba Daily News texts positioned female actors in subject and object position in their news texts. Women as non-marginalized subject found in three news texts. Women as non-marginalized objects found in two news texts. Women in the marginalized object position found in eight news texts. Marginalization was conducted by using exclusion and inclusion strategies. The exclusion strategy used includes the nomination and substitution of clauses. Inclusion strategies used were differentiation-indifferentiation, objectivity-abstraction, nomination-identification, nomination-categorization, and association-disassociation. In addition, the use of certain vocabularies can marginalize the position of women in the daily news text Prohaba.